Fluency, flexibility and originality in thinking towards managerial empowerment and sustainable development - Panchanatham, N. (university of Jaffna, 2014)
Honorable Dignitaries on the Dias, Great academicians, Learned participants, Ladies and Gentlemen. The University of Jaffna, Sri Lanka is known for its academic excellence all over the world. I appreciate the efforts taken by the Faculty of Management Studies and Commerce University of Jaffna, Sri Lanka for conducting an International Conference on Contemporary Management during March 14-15, 2014. The conference will address on various sub themes of contemporary management and also focus on empowering people towards sustainable development. My address would cover certain issues relating to the theme of the conference in general and very particularly on empowering people to think creatively and working towards sustainable development. In creativity research, terms such as fluency, flexibility and originality are used to describe different aspects of creative thinking. Fluency is the number of thoughts or ideas generated. Flexibility is the number of different perspectives or fields your ideas come from. Creativity is defined as the act of bringing into existence something which did not exist before, and empowerment is defined as an individual's belief in his/her ability to exercise choice. Facilitating creative collaboration is one of the most important management roles in leading a creative environment. In particular, empowering a team with critical and creative thinking facilitates innovation effort that draws out new exciting ideas from the team. Empowerment refers to increasing the economic, political, social, educational, gender, or spiritual strength of individuals and communities. More empowered teams are also more productive and proactive than less empowered teams and have higher levels of customer service, job satisfaction, and organizational and team commitment.